Bahasa Inggris - Medina Sophia Pratiwi; Jumadi; Mega Safana (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to see the effectiveness of e-learning based learning media on critical thinking skills. The method used is a literature review with a qualitative approach. This study describes the development of technology as a challenge for the world of education to continue to innovate in the learning process so that it can remain balanced with the demands of the 4.0 Learning media is an effort to optimize the abstract learning process into reality. The use of learning media is now increasingly modern based on e-learning which utilizes the internet so that it can be used and accessed easily. The use of e-learning based learning media can improve critical thinking skills in the industrial revolution 4.0. Judging from the studies that have been presented, the use of media greatly helps educators in the teaching and learning process, especially in abstract lessons that can be visualized through learning media.